A Study on Correlation Between Serum Cholinesterase Level and Clinical Severity Based on Pop Scale in Organophosphorus Poisoning - Shrestha, Anil; Kidwai, Aasim; Shrestha, Richa; KC, Suman (Journal of Nepalgunj Medical College, 2021)
Introduction: Organophosphorus (OP) compounds are the most commonly used pesticides worldwide and Organophosphorus poisoning has become the major public health problem especially in developing countries.The case fatality rate following ingestion of Organophosphorus pesticides in developing countries in Asia is 5-20%.Due to limited availability of facilities and resources in Nepal, it is important to prioritize treatment based on severity of poisoning as all patients can’t be managed in Intensive Care Unit.Aims: To study the correlation between serum cholinesterase level and clinical severity based on Peradenya organophosphorus poisoning scale in Organophosphorus poisoning.Methods: The study was conducted in the department of Medicine, Nepalgunj Medical College, Kohalpur, Banke from November 2019 to November 2020. It is based on the descriptive study of 66 patients with Organophosphorus poisoning attending to the emergency department. All patients with history of exposure to Organophosphorus poisoning were included in the study. Peradenya Organophosphorus Poisoning scale was used to assess the clinical severity as mild, moderate and severe. At the same time venous blood samples were collected for serum cholinesterase level.Results: Age group ranged from 16-60 years and majority of patients were in the age group of 20-29 years (34.85%). 53% were females. 74.2% of the patients were from lower socioeconomic status. 83.3% of the patients consumed poison with suicidal intention. Majority of the patients were from tharu ethinicity (40.9%) and were farmers (30.3%). It was observed that there is significant correlation between serum cholinesterase level and severity of poisoning based on Peradenya Organophosphorus Poisoning scale at initial presentation (p value